2017
DOI: 10.1016/j.comnet.2017.05.018
|View full text |Cite
|
Sign up to set email alerts
|

An architecture and protocol for smart continuous eHealth monitoring using 5G

Abstract: Continuous monitoring of chronic patients improves their quality of life and reduces the economic costs of the sanitary system. However, in order to ensure a good monitoring, high bandwidth and low delay are needed. The 5G technology offers higher bandwidth and lower delays and packets loss than previous technologies. This paper presents an architecture for smart eHealth monitoring of chronic patients. The architecture elements include wearable devices, to take measures from the body, and a smartphone in the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
68
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 127 publications
(68 citation statements)
references
References 23 publications
0
68
0
Order By: Relevance
“…However, for large number of users, 4G LTE suffers from high delay and high packet loss. The work presented in [25] revealed that the efficiency of 4G LTE decreases dramatically as the amount of traffic increases.…”
Section: Limitations Of 4g Ltementioning
confidence: 99%
“…However, for large number of users, 4G LTE suffers from high delay and high packet loss. The work presented in [25] revealed that the efficiency of 4G LTE decreases dramatically as the amount of traffic increases.…”
Section: Limitations Of 4g Ltementioning
confidence: 99%
“…Sandhu et al [11] provided a mobile model in BAN and presented a mathematical model in order to stimulate nodes due to changing state. Yousaf et al [4] introduced CEMob and emergency transfer of data to support mobility in BANs. Their work in this area reflects the fact that the proposed protocol CEMob, used as a routing layer protocols, to support network critical data transfers to emergency services with mobility in BANs.…”
Section: Related Workmentioning
confidence: 99%
“…In the case of communication, nodes that are far from the sink are less likely to be depleted, while in the multi-hop communication manner, the energy consumption of the nodes which are closer to the sink is higher than other nodes. Another challenge in this regard is the fact that in designing, routing protocols should consider the energy consumption and link utilization [4].…”
Section: Introductionmentioning
confidence: 99%
“…ZigBee is popular for monitoring systems where a great number of nodes and low energy consumption are required. Services that require interaction with humans are usually utilized with PCs, smartphones or tablets, such as Ambient Assisted Living (AAL) and healthcare systems, and employ WiFi or mobile communications [9,10]. Rural areas are usually connected through WiMax as it provides a wireless communication for longer distances.…”
mentioning
confidence: 99%
“…The channel bandwidth is from 1,75 to 20 MHz. The lower data rates reach up to 15 Mbps Vol 10,No. 1.…”
mentioning
confidence: 99%